Avaliação do efeito gastroprotetor da locust bean gum (Ceratonia siliqua linn) & galactomanana de cassia fistula no modelo de gastrite aguda experimental induzida por etanol - Freire, Paulo Roberto Pavão (2022)
Gastritis is defined as a change in the stomach mucosa, mainly influenced by poor intake of food content or harmful substances such as ethanol. This pathology currently has interventions with several limitations. Therefore, the present study aimed to evaluate the possible gastroprotective effects of Locust Bean Gum (LBG) & galactomannans from Cassia Fistula (GMNN from CF) against the action of ethanol on the gastric mucosa of Swiss mice, in which they were divided ( n of 6) in groups: saline, omeprazole (OME - 40mg/kg), gastric lesion (LG - 50% ethanol) and pre-treated with LGB, GMNN of CF at doses of 5, 10 and 30 mg/kg, with subsequent macroscopic and histological analyses, measurement of myeloperoxidase (MPO), reduced glutathione (GSH), levels of malonaldehyde (MDA), tissue hemoglobin and pro-inflammatory cytokines (TNF-α and IL-1β) in the animals' stomachs. Initial analyzes of the stomach tissue of animals pre-treated with galactomannans at doses of 5, 10 and 30mg/kg, respectively, showed that LBG (32, 34 and 28%) and CF GMNN (36, 29 and 21%), highlighted significantly (p<0.05) less significant rates of hemorrhagic lesions than the LG group, which were similar to the OME group (33%). As for the histological data, the ability of LBG and GMNN of CF to significantly reduce (p<0.05) alterations such as edema, loss of epithelial cells and cellular infiltrate was shown, with the exception of hemorrhage for the LBG group, when compared to the LG group. MPO levels were reduced during pretreatment analyzes with OME (46%) and similarly and statistically significantly (p<0.05) in the LBG (50, 58 and 48%) and CF GMNN groups (46, 44.7 and 48%), at doses of 5, 10 and 30mg/kg. The measurements of GSH indices were reduced in the LG group (73%), and its consumption was lower only with the treatment with OME (124%), with no significant modulating activity (p<0.05) of LBG (99.102 and 92%) and CF GMNN (97, 93 and 111%) in the initial doses. However, in view of the MDA analyzes at the concentrations mentioned above, LBG (31, 59 and 40%) and CF GMNN (38, 52 and 43%) are shown to be effective in statistically reducing (p<0.05) their indices, and as expected in pretreatment with OME (41%). Based on the results, the dose of 10mg/kg was chosen to continue the tissue hemoglobin tests, where statistically (p<0.05) reduced levels were observed in the OME (64%) and GMNN CF groups (79%), and this effect was not observed for the LBG group (120%); and to measure the levels of pro-inflammatory cytokines, in which the IL-1β analyzes were significantly (p<0.05) reduced for the OME groups, and in the pre-treatments with LBG and GMNN of CF. While the TNF-α indices are shown to be significantly (p<0.05) reduced only in the OME and LBG groups. Given the above, it is possible to observe the gastroprotective effects of LBG and GMNN of CF by reducing harmful, hemorrhagic, inflammatory aspects and oxidative stress parameters, in MDA levels.